2010
DOI: 10.2169/internalmedicine.49.2551
|View full text |Cite
|
Sign up to set email alerts
|

Response of Serum Carboxylated and Undercarboxylated Osteocalcin to Risedronate Monotherapy and Combined Therapy with Vitamin K2 in Corticosteroid-Treated Patients: A Pilot Study

Abstract: Objective The aim of this study was to investigate the responses of serum osteocalcin (OC), undercarboxylated osteocalcin (ucOC)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…When treated with corticosterone, WT mice displayed a decrease in the level of both total and undercarboxylated osteocalcin but no change in the proportion of undercarboxylated osteocalcin. This mimics observations in humans treated with glucocorticoids (52). It has also been reported that both the vitamin K-dependent carboxylase activity and the biosynthesis of its substrates are enhanced by glucocorticoids (53,54).…”
Section: Figure 13supporting
confidence: 83%
“…When treated with corticosterone, WT mice displayed a decrease in the level of both total and undercarboxylated osteocalcin but no change in the proportion of undercarboxylated osteocalcin. This mimics observations in humans treated with glucocorticoids (52). It has also been reported that both the vitamin K-dependent carboxylase activity and the biosynthesis of its substrates are enhanced by glucocorticoids (53,54).…”
Section: Figure 13supporting
confidence: 83%
“…Further, inhibitors of bone resorption decrease serum unOC in patients with osteoporosis[36]. Overall, unOC is associated with bone turnover markers in adults and decreases with corticosteroid treatments[37, 38]. However, the associations of unOC with resorption in early development may be different than in adults.…”
Section: 0 Discussionmentioning
confidence: 99%
“…Finally, one of the major hormones to release energy-rich fuels from storage sites, namely glucocorticoid, reduces osteocalcin levels in that it inhibits osteoblast function [37]. This is another indication of the storage function of this hormone that can be switched off by a hormone of the energy expenditure network.…”
Section: Energy Storage Hormonesmentioning
confidence: 99%